2017
DOI: 10.1111/bju.13786
|View full text |Cite
|
Sign up to set email alerts
|

Detection of prostate cancer using magnetic resonance imaging/ultrasonography image‐fusion targeted biopsy in African‐American men

Abstract: Our key finding confirms a lack of racial difference in the detection rate of overall prostate cancers and CSPC with MRI/US FTB between A-A and Caucasian men. MRI/US FTB detected more CSPC using fewer cores compared with random biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Multi-parametric MRI (mpMRI) for prostate cancer detection in AA men was evaluated in a retrospective study that included 117 AA and 544 CA men. In this study, there was no racial difference in the detection rate of overall prostate cancers or clinically significant prostate cancers between AA and CA men on mpMRI ( 31 ). Another study including 822 men (127 AA) found that MRI/ultrasound-guided fusion biopsy demonstrated increased diagnostic yield in the AA population in an age- and PSA-matched cohort of CA patients ( 32 ).…”
Section: Diagnostic Modalities For Prostate Cancer In African Americamentioning
confidence: 48%
“…Multi-parametric MRI (mpMRI) for prostate cancer detection in AA men was evaluated in a retrospective study that included 117 AA and 544 CA men. In this study, there was no racial difference in the detection rate of overall prostate cancers or clinically significant prostate cancers between AA and CA men on mpMRI ( 31 ). Another study including 822 men (127 AA) found that MRI/ultrasound-guided fusion biopsy demonstrated increased diagnostic yield in the AA population in an age- and PSA-matched cohort of CA patients ( 32 ).…”
Section: Diagnostic Modalities For Prostate Cancer In African Americamentioning
confidence: 48%
“…However, Shin et al . reported there was a 47% detection rate of prostate cancer among MRUS TB biopsied Likert score 3 in African American patients, 55% of those were clinically significant cancer . Because there is significant variability in the detection rate of prostate cancer in biopsied Likert score 3 lesions, how to manage patients with Likert score 3 lesions remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…17 Prostate MRI may identify suspicious regions in the prostate to target for subsequent biopsy, significantly increasing the likelihood of identifying clinically meaningful prostate cancer, 18 and prostate cancer detection by MRI-targeted biopsy is not significantly different between Black vs White patients. 19 Additionally, a prostate MRI may obviate the need for biopsy, thus decreasing the overdiagnosis of insignificant prostate cancer. 20 The American Urological Society (AUA) and National Comprehensive Cancer Network have both recognized the important role of prostate MRI for prostate cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, prostate magnetic resonance imaging (MRI) has emerged as a means to evaluate men with an elevated PSA before possible prostate biopsy and its use is rapidly increasing nationally . Prostate MRI may identify suspicious regions in the prostate to target for subsequent biopsy, significantly increasing the likelihood of identifying clinically meaningful prostate cancer, and prostate cancer detection by MRI-targeted biopsy is not significantly different between Black vs White patients . Additionally, a prostate MRI may obviate the need for biopsy, thus decreasing the overdiagnosis of insignificant prostate cancer …”
Section: Introductionmentioning
confidence: 99%